Natural enemies associated with Maconellicoccus hirsutus (Hemiptera: Pseudococcidae) in the state of Sao Paulo, Brazil - Peronti, Ana Lucia B. G. [UNESP]; Martinelli, Nilza Maria [UNESP]; Alexandrino, Julia Godoy [UNESP]; Marsaro Junior, Alberto Luiz; Penteado-Dias, Angelica Maria; Almeida, Lucia M. (Florida Entomological Soc, 2016)
The pink hibiscus mealybug, Maconellicoccus hirsutus (Green) (Hemiptera: Pseudococcidae), occurs widely in Brazil, causing damage to some crops. However, information on beneficial insects acting to control populations of this pest in Brazil is practically non-existent. A survey was conducted in the state of Sao Paulo. The insect associates of M. hirsutus recorded on Hibiscus rosa-sinensis L. (Malvales: Malvaceae) were the parasitoid Gyranusoidea indica Shafee, Alam & Agarwal (Hymenoptera: Encyrtidae) and the predators Cycloneda sanguinea (L.), Cryptolaemus montrouzieri Mulsant, Chilocorus nigrita (F.), Exoplectra sp., Harmonia axyridis (Pallas), Tenuisvalvae notata (Mulsant) (Coleoptera: Coccinellidae), and Ceraeochrysa sp. (Neuroptera: Chrysopidae). Cryptolaemus montrouzieri was the most commonly collected species on populations of M. hirsutus infesting plants of H. rosa-sinensis. Chilocorus nigrita, Exoplectra sp., H. axyridis, T. notata, and Ceraeochrysa sp. were associated for the first time with M. hirsutus, and G. indica was recorded for the first time in Brazil.
Keywords: invasive species; geographical distribution; biological control; parasitoid; predator